(untitled) (Physical Education, Health and Social Sciences, 2026)
This research focuses on creating an intelligent packaging system using gelatin and chitosan and incorporating anthocyanins from purple cabbage, eggplant peel, and black currant as color indicators. The film developed aim to monitor fish spoilage and freshness in real time, utilizing anthocyanin sensitivity to pH changes as a visual indication. The study reveals that as anthocyanin concentration increases, film thickness and viscosity rise significantly. Transparency remains above 75%, ensuring clear visibility and effective color indication. Water vapor permeability decreases with concentration, ranging from 2.03±0.08g/m2 to 6.69±0.09 g/m2. Anthocyanin-based pH indicators exhibit color changes, with the highest pH observed on the 7th day. The color changes observed were pink spots at acidic pH, mustard orange color at neutral pH and dark green spots at slightly basic pH. Porosity increases with concentration, ranging from 0.19±0.04% to 0.40±0.04%. Overall, these films, particularly the CGA-EPP based film shows greater efficiency as eggplant peel consist of higher anthocyanin content compared to other two sources. This proves film to be beneficial for the food industry, offering a quick and cost-effective method for determining fish spoilage and freshness through color indication and minimizing the need for further testing.